IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN HARIAN DI SDN ULU BENTENG 4 KAB. BARITO KUALA TAHUN PELAJARAN 2025/2026 - Ikhsan Kholiq, Muhammad; Hermaniar, Yulieda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education in primary schools plays a crucial role that is imparted not only through classroom instruction, but also through daily routine habits practiced consistently (Rahmah, Suriansyah, & Harsono, 2025; Hidayati, 2020). However, in practice, the execution of daily activities in schools often remains merely an administrative routine and has not fully succeeded in deeply internalizing character values within students (Indrianingrum, Miyono, & Nurhayati, 2024). This condition necessitates more targeted management to ensure that daily habits genuinely have a significant impact on students' moral development (Suryadi & Maulida, 2023). This study aims to analyze in depth the implementation of character education through daily activities at SDN Ulu Benteng 4, Barito Kuala Regency, during the 2025/2026 academic year (Sugiyono, 2020). The main focus of this study is to identify the forms of activities, the character values instilled, as well as the obstacles and optimization efforts in shaping student character through daily habits in the school environment (Moleong, 2021). This study employed a qualitative approach with a descriptive design, involving the school principal, classroom teachers, and students as research subjects. Data collection techniques included observation, interviews, and documentation, which were subsequently analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing (Miles, Huberman, & Saldana, 2014; Rahmah et al., 2025).The results showed that the implementation of character education at the school encompasses structured, unstructured, and specialized habitual activities that embody values such as discipline, responsibility, cooperation, and mutual respect (Indrianingrum et al., 2024). Students demonstrated positive behavior through daily practices such as class duty shifts, a culture of greetings and polite behavior, and orderly queuing. Nevertheless, challenges persist, including a lack of implementation consistency, limited supervisors, and sub-optimal involvement from all school members (Rahmah et al., 2025). Therefore, daily activities need to be developed in a more innovative, reflective, and sustainable manner so that character internalization can be achieved.